2023
DOI: 10.12911/22998993/161013
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Greenhouse Gas Emissions by Replacing Fertilizers with Digestate

Abstract: Digestate from a biogas plant can be a valuable organic and mineral fertilizer. Quantitative proportions of cosubstrates used in three agricultural biogas plants in Poland were analyzed. The composition of digestates was examined and large differences in the content of macronutrients were found, especially N and K. On the basis of the factors used to calculate emissions from the production and use of artificial fertilizers, the greenhouse gas (GHG) reduction resulting from replacing mineral fertilizers with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It seems that methane fermentation combined with energy recovery in a CHP unit is the most advantageous solution in terms of sustainable development assumptions [7,104,105]. The weakness, however, as shown in this study and as can be found in the literature sources, is the biogas efficiency of manure [106,107].…”
Section: Discussionmentioning
confidence: 63%
“…It seems that methane fermentation combined with energy recovery in a CHP unit is the most advantageous solution in terms of sustainable development assumptions [7,104,105]. The weakness, however, as shown in this study and as can be found in the literature sources, is the biogas efficiency of manure [106,107].…”
Section: Discussionmentioning
confidence: 63%
“…According to the results This practice may increase biomass yield and could be considered the equivalent of mineral fertilisers. Kowalczyk-Juśko et al (2023) considered digestate as an organo-mineral fertiliser and valuable exogenous organic material. If there is not a consistent supply of organic materials to the soil, its fertility will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The harmfulness of CO 2 has a secondary nature and exhibits through a significant impact on the greenhouse effect [Gonzalez-Salazar et al 2018]. The significance of the emission of CO 2 is currently analyzed in terms of its share in the energy balance of combustion of fossil fuels not only in the emerging economies such as China or India but also traditional fossil fuel-based economies (USA), in which carbon dioxide is the main component of the flue gas [Kowalczyk-Juśko et al 2023]. The current assumption and prospects for the coming years for the European Union is to limit global warming by maximum 1.5°C, which is directly related to the limitation in the emission of CO 2 to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%